2023
DOI: 10.1038/s41598-023-36232-y
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in bumble bee larvae differs qualitatively between high and low concentration imidacloprid exposure levels

Abstract: Neonicotinoid pesticides negatively impact bumble bee health, even at sublethal concentrations. Responses to the neonicotinoid imidacloprid have been studied largely at individual adult and colony levels, focusing mostly on behavioral and physiological effects. Data from developing larvae, whose health is critical for colony success, are deficient, particularly at the molecular level where transcriptomes can reveal disruption of fundamental biological pathways. We investigated gene expression of Bombus impatie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…A recent study using next-generation sequencing has indicated that sublethal imidacloprid treatment during the larval stage causes changes in gene expression in larvae, pupae, and adults, suggesting a persistent sublethal impact on honey bee development ( Chen et al, 2021 ). Furthermore, a latest study has demonstrated that imidacloprid induces differential gene expression in bumble bee larvae, resulting in unique expression patterns related to various biological processes such as starvation response, cuticle genes, neural development, and cell growth ( Martín-Blázquez et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study using next-generation sequencing has indicated that sublethal imidacloprid treatment during the larval stage causes changes in gene expression in larvae, pupae, and adults, suggesting a persistent sublethal impact on honey bee development ( Chen et al, 2021 ). Furthermore, a latest study has demonstrated that imidacloprid induces differential gene expression in bumble bee larvae, resulting in unique expression patterns related to various biological processes such as starvation response, cuticle genes, neural development, and cell growth ( Martín-Blázquez et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The field-realistic concentration of imidacloprid found in nectar is 10 ppb [ 33 , 34 ] which means that, given the fact that a bumblebee worker consumes in a full day 150–300 μL of nectar, a worker ingests 1,5–3 ng of imidacloprid/day [ 35 ]. The findings of these studies show that exposure to field-realistic concentrations of neonicotinoids can impair their physiology [ 36 , 37 , 38 ], behaviour [ 20 , 35 , 37 , 39 , 40 , 41 , 42 ], and colony survival [ 22 , 43 , 44 , 45 ]. Among all of these studies, there are some that focus on the sublethal effects of field-realistic concentration of neonicotinoids on bumblebee flight and forage activity.…”
Section: Introductionmentioning
confidence: 99%